Humoral immune failure defined by immunoglobulin class and immunoglobulin G subclass deficiency is associated with shorter treatment‐free and overall survival in Chronic Lymphocytic Leukaemia. (21st February 2018) - Crassini, Kyle R.; Zhang, Eva; Balendran, Shalini; Freeman, Jane A.; Best, O. Giles; Forsyth, Cecily J.; Mackinlay, Naomi J.; Han, Ping; Stevenson, William S.; Mulligan, Stephen P.
Summary: Immune dysfunction attributed to hypogammaglobulinaemia is common in chronic lymphocytic leukaemia (CLL) and infection is a major contributor to morbidity and mortality. A higher incidence of multiple immunoglobulin and immunoglobulin G (IgG) subclass deficiency was associated with more advanced disease ( P  < 0·001 and P  < 0·001, respectively) in a cohort of 147 CLL patients. Multiple immunoglobulin and IgG subclass deficiency were significantly associated with shorter treatment‐free survival (TFS) ( P  < 0·001 and P  = 0·006, respectively). The association between disease stage and immune dysfunction demonstrated by these data suggest aspects of immune deficiency correlate with disease severity and may be associated with shorter TFS in CLL.